Prostate Cancer: Shifting from Morphology to Biology - Staibano, Stefania (Springer Netherlands : Imprint: Springer, 2013)
The aim of this book will be to contribute to the education of a new generation of experts in urology, molecular biology, pathology and oncology, offering them sufficient knowledge in basic and translational research to be fluency in the web of interacting networks playing a role in prostate cancer development, progression, metastasis and drug-resistance.The volume will cover the latest innovative researches in prostate cancer, with particular emphasis to the state-of-the-art analysis technologies that are essential for the accurate identification of molecular targets for disease diagnosis, molecular mechanisms of tumorigenesis, markers for susceptibility, molecular-based prognostic prevision, characterization of biomarkers of drug efficacy and drug resistance, validation of new therapeutics and diagnostics. Current advancements on the intersecting data concerning transcriptomes, proteomes, and the molecular techniques referred as "omes", will be reported and discussed.